A case report of rare pancreatic lymphoma: wide range of diffuse large B-cell lymphoma located in the body and tail of pancreas - Song, Xiang; Hu, Weiyu; Zhang, Li; Mao, Tao; Zhu, Yingli; Chen, Xiaokai; Ren, Linlin (Frontiers in Oncology, 2025)
BackgroundPancreatic lymphoma is a rare pancreatic malignancy that is challenging to differentiate from diseases such as pancreatic cancer (PC). Although pathological examination of specimens obtained through surgery or endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) can aid in diagnosis, factors such as the occasional need for surgery and the variability in specimen quality from EUS-FNA complicate the diagnostic process. Misdiagnosis of pancreatic lymphoma as PC often leads to unnecessary surgery. In addition, surgical intervention may be necessary as a second-line treatment option for pancreatic lymphoma patients presenting with severe gastrointestinal symptoms. However, an optimal postoperative treatment strategy remains undefined, particularly in cases with extensive invasion, thereby impacting long-term survival. This lack of consensus underscores the need for further research to establish evidence-based therapeutic protocols.Case DescriptionWe present the case of a 55-year-old patient (abdominal pain for over one month, intensified for two weeks). Imaging studies suggested a hypodense mass in the tail of the pancreas with ill-defined margins extending to the spleen, as well as a hypodense lesion within the spleen. The patient underwent surgical intervention, and postoperative pathological analysis confirmed the diagnosis of diffuse large B-cell lymphoma (DLBCL). Following surgery, the patient was initially treated with a short-term C2PET oral chemotherapy regimen, which was subsequently transitioned to the R-CHOP regimen. This therapeutic approach resulted in a favorable outcome, with the patient achieving a 5-year survival period. As far as we know, this may be the first reported case of pancreatic lymphoma with such a widespread involvement, in which patient underwent surgery and postoperative chemotherapy and obtained a 5-year survival period.Literature ReviewWe reviewed previously reported cases of the DLBCL pancreatic lymphoma located in the body and tail of pancreas, and conducted a comparative analysis.Purposes and Clinical RelevanceOur objectives are twofold: first, to highlight the critical role of preoperative EUS-FNA and positron emission tomography–computed tomography in the diagnostic evaluation for patients with pancreatic mass and suspected lesions in immune-associated organs; and second, to propose evidence-based recommendations for postoperative chemotherapy in cases of DLBCL involving the pancreas.